2007
DOI: 10.1152/japplphysiol.00182.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spleen and cardiovascular function during short apneas in divers

Abstract: We investigated the spleen volume changes as related to the cardiovascular responses during short-duration apneas at rest. We used dynamic ultrasound splenic imaging and noninvasive photoplethysmographic cardiovascular measurements before, during, and after 15-20 s apneas in seven trained divers. The role of baroreflex was studied by intravenous bolus of vasodilating drug trinitrosan during tidal breathing. The role of lung volume was studied by comparing the apneas at near-maximal lung volume with apneas afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 22 publications
10
48
4
Order By: Relevance
“…At the beginning of apnoea, the immediate response consisted of a rapid fall of SBP and DBP, as previously observed at rest (Andersson and Schagatay, 1998;Palada et al, 2007;Perini et al, 2008) and at exercise (Sivieri et al, 2015). This fall was associated with a reduction of SV, supporting the notion that the fall of SBP may be due to an acute reduction of venous return related to the act of holding the breath at elevated lung volumes (Andersson and Schagatay, 1998).…”
Section: The Characteristics Ofsupporting
confidence: 68%
“…At the beginning of apnoea, the immediate response consisted of a rapid fall of SBP and DBP, as previously observed at rest (Andersson and Schagatay, 1998;Palada et al, 2007;Perini et al, 2008) and at exercise (Sivieri et al, 2015). This fall was associated with a reduction of SV, supporting the notion that the fall of SBP may be due to an acute reduction of venous return related to the act of holding the breath at elevated lung volumes (Andersson and Schagatay, 1998).…”
Section: The Characteristics Ofsupporting
confidence: 68%
“…Then SBP returned to control values within the end of phase I, whereas DBP increased by about 8 mmHg above pre-apnoea values. Transient hypotension at the beginning of dry apnoea was previously reported Palada et al 2007), and was attributed to the reduction of venous return due to holding the breath. The Wnal result of the BP changes was an increase in MBP by about 8-10% at the end of phase I, comparable to previous data obtained during dry apnoeas lasting 30 s (Leuenberger et al 2001) and 60 s (Andersson et al 2000).…”
Section: Discussionmentioning
confidence: 68%
“…Blood Xow is likely redistributed toward vital organs, whereas peripheral tissues may be unperfused so that lactate is accumulated in them. Spleen contraction may also occur (Bakovic et al 2003;Palada et al 2007). The ensemble of these changes, generally referred to as diving response, is interpreted as an O 2 -conserving mechanism (Ferretti 2001;Foster and Sheel 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, larger heart rate during dynamic apnea when compared to static apnea indicates larger sympathetic activity. In addition, we and others have suggested that splenic contraction is also a part of diving response [14,21] and that it occurs even with very short breath-holds lasting only 15 s, without the presence of chemical stimuli like hypoxia and/or hypercapnia [22].…”
Section: Physiological Diving Responsementioning
confidence: 84%